Induksi Kalus Daun Stevia (Stevia rebaudiana) Pada Berbagai Kombinasi 2,4D dan BAP Secara In Vitro - Riski Busaifi; Hirjani Hirjani; Riska Lestari (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2021)
Stevia plant is one of the sweetener plants besides sugarcane, stevia plant leaves are estimated to be 300 times sweeter than sugar. But Stevia is constrained by the propagation of cuttings produced slightly in the provision of seedlings on a large scale. So, the tissue culture technique is one of the alternatives. The combination of auxedine and cytokinin has an important role in inducing callus where 2.4 D and BAP is a combination used in in-vitro plant propagation. The purpose of this study is to find the optimal 2.4D and BAP concentrations for the growth of stevia leaf calluses. The explant used from the young leaves of a healthy stevia plant comes from the field then grown on MS media with a combination of 2.4-D (0.5; 1; 1.5; and 2 mg/l) and BAP (0.5; 1; and 1.5 mg/l) to induce embryogenic callus. The observed variables include Leaf Curved Day, Callus Appear Day, Weight, Color. and its texture. Treatment of 2.4-D 2 mg / L with BAP 0.5 mg / L BAP is able to produce good callus, many, initiation is fast and efficient (optimal).